The (totally not) guaranteed guide to popularity, prettiness & perfection - McCafferty, Megan (McCafferty, Megan. Jessica Darling's it list, 2014)
On the first day of seventh grade, Jessica discovers she has remained largely the same while her friend has become cute and popular. Worried she will be left behind as he friend embarks on a new path, Jessie wonders what she should do and eventually learns the value of being oneself.